1999
DOI: 10.1038/sj.onc.1202515
|View full text |Cite
|
Sign up to set email alerts
|

Centrosome hyperamplification in human cancer: chromosome instability induced by p53 mutation and/or Mdm2 overexpression

Abstract: We have previously reported that loss of p53 tumor suppressor protein results in centrosome hyperampli®ca-tion, which leads to aberrant mitosis and chromosome instability. Since p53 is either deleted or mutated in human cancers at a high frequency, we investigated whether human cancers showed centrosome hyperampli®cation. Screening of advanced stage breast ductal carcinomas and squamous cell carcinomas of the head and neck (SCCHN) revealed that centrosome hyperampli®cation is frequent in both tumor types. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
202
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(213 citation statements)
references
References 51 publications
9
202
2
Order By: Relevance
“…Six (55%) of 11 G:C-to-A:T transitions occurred at CpG dinucleotides in five hot-spot codons (175, 245, 248, 273, and 282), and it was suggested that specific p53 mutations participate in the progression of human prostate cancer and may be predictive of metastasis (10). This study, in addition to some other recent studies (both in vitro and in vivo), has demonstrated correlation between loss or mutation of p53 and the presence of CI (53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). More recently, centrosome hyperamplification was found to be the major mechanism responsible for CI in vitro and in vivo (58, 59, 64 -66).…”
Section: Figure 2 P53 Ihc (Do7)supporting
confidence: 55%
See 1 more Smart Citation
“…Six (55%) of 11 G:C-to-A:T transitions occurred at CpG dinucleotides in five hot-spot codons (175, 245, 248, 273, and 282), and it was suggested that specific p53 mutations participate in the progression of human prostate cancer and may be predictive of metastasis (10). This study, in addition to some other recent studies (both in vitro and in vivo), has demonstrated correlation between loss or mutation of p53 and the presence of CI (53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). More recently, centrosome hyperamplification was found to be the major mechanism responsible for CI in vitro and in vivo (58, 59, 64 -66).…”
Section: Figure 2 P53 Ihc (Do7)supporting
confidence: 55%
“…Breast carcinoma and squamous cell carcinoma of the head and neck with either p53 deletion or mutation show centrosome hyperamplification (58,64,65).…”
Section: Figure 2 P53 Ihc (Do7)mentioning
confidence: 99%
“…In particular, centrosomal aberrations have been correlated with a number of different genetic abnormalities in tumours, e.g. amplification of STK15 (Zhou et al, 1998), mutations in TP53 (Carroll et al, 1999), and inactivation of BRCA1 (Xu et al, 1999), BRCA2 (Tutt et al, 1999), and GADD45 (Hollander et al, 1999). In adenocarcinomas of the prostate and breast, centrosomal abnormalities are known to increase in parallel to loss of tissue differentiation and the development of aneuploidy (Pihan et al, 2001;Lingle et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Breast and prostate cancer [45][46][47] Bladder cancer and Malignant biliary tract disease [48,49] Pancreatic cancer [50] Head and neck sguamous cell carcinoma Oral squamous carcinomas [51][52][53] Neuroectodermals tumours [54] these were found centrosome hyperamplification. Since the percentage is so high, it is implied that this could be used as a marker for HNSCC [51].…”
Section: Abnormalities In Centrosomes In Various Cancersmentioning
confidence: 99%
“…This observation is also interesting because of the fact that the p53 suppressor gene, the most frequently mutated in gene human cancers, is correlated with centrosome hyperamplification in HNSCC. Centrosome hyperamplification is either observed in p53 mutant tumours or in tumours that retain wild type p53 but contain overexpressed Mdm2, an oncogene that inhibits p53 transactivation function [52]. Centrosomal abnormalities have also been found increased in oral squamous cell carcinomas in cells in which the spindle checkpoint protein CDC20 is overexpressed [53].…”
Section: Abnormalities In Centrosomes In Various Cancersmentioning
confidence: 99%